Rise of Mucormycosis during the COVID-19 Pandemic and the Challenges Faced - Malavika Kottarathil; Thayanidhi Premamalini; Sathyamurthy P; Anupma Kindo (Mazandaran University of Medical Sciences, 2023)
Mucormycosis (previously called zygomycosis) is a diverse group of increasingly recognized and frequently fatal mycotic diseases caused by members of the class zygomycetes. Mucormycosis is around 80 times more common in India, compared to other developed countries, with a frequency of 0.14 cases per 1,000 population. The most frequent causative agent of mucormycosis is the following genera from the Order Mucorales: Rhizopus, Mucor, Rhizomucor, Absidia, Apophysomyces, Cunninghamella, and Saksenaea. The major risk Mucormycosis (previously called zygomycosis) is a diverse group of increasingly recognized and frequently fatal mycotic diseases caused by members of the class zygomycetes. Mucormycosis is around 80 times more common in India, compared to other developed countries, with a frequency of 0.14 cases per 1,000 population. The most frequent causative agent of mucormycosis is the following genera from the Order Mucorales: Rhizopus, Mucor, Rhizomucor, Absidia, Apophysomyces, Cunninghamella, and Saksenaea. The major risk factors for the development of mucormycosis are diabetic ketoacidosis, deferoxamine treatment, cancer, solid organ or bone marrow transplantations, prolonged steroid use, extreme malnutrition, and neutropenia. The common clinical forms of mucormycosis are rhino-orbital-cerebral, pulmonary, cutaneous, and gastrointestinal. During the second wave of COVID-19, there was a rapid increase in mucormycosis with more severity than before. Amphotericin B is currently found to be an effective drug as it is found to have a broad spectrum activity and posaconazole is used as a salvage therapy. Newer triazole isavuconazole is also found effective against mucormycosis. This article aimed to review various studies on the laboratory diagnosis and treatment of mucormycosis.